Tolerance in Economic Democracy Between Majority and Minority Religious Groups - Mu’di, Ahmad; Balya, Toifur Ahmad (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
This study examines the practice of tolerance in the sphere of economic democracy between muslims and hindus in Pengalangan village, Menganti, Gresik. The research focuses on interreligious economic interactions that reflect harmony and social solidarity. Its objective is to understand the forms, dynamics, and contributions of economic tolerance to the community’s social cohesion. A qualitative case study approach was applied, with data gathered through observation, in-depth interviews, and documentation. The participants included religious leaders, small-scale entrepreneurs, and local residents from both faiths. Findings reveal that tolerance is manifested through trade cooperation, mutual support among micro-enterprises, and the avoidance of conflict in market exchanges. In conclusion, the people’s economy in the village serves as a strategic arena for reinforcing social cohesion across religious boundaries through everyday economic practices.